Effects of Hypericum Perforatum, in a rodent model of periodontitis - Paterniti, Irene (BioMed Central, 2010)
BACKGROUND: Hypericum perforatum is a medicinal plant species containing many polyphenolic compounds, namely flavonoids and phenolic acids. In this study we evaluate the effect of Hypericum perforatum in animal model of periodontitis. METHODS: Periodontitis was induced in adult male Sprague-Dawley rats by placing a nylon thread ligature around the lower 1st molars. Hypericum perforatum was administered at the dose of 2 mg/kg os, daily for eight days. At day 8, the gingivomucosal tissue encircling the mandibular first molar was removed. RESULTS: Periodontitis in rats resulted in an inflammatory process characterized by edema, neutrophil infiltration and cytokine production that was followed by the recruitment of other inflammatory cells, production of a range of inflammatory mediators such as NF-κB and iNOS expression, the nitration of tyrosine residues and activation of the nuclear enzyme poly (ADP-ribose) polymerase; apoptosis and the degree of gingivomucosal tissues injury. We report here that Hypericum perforatum exerts potent anti-inflammatory effects significantly reducing all of the parameters of inflammation as described above. CONCLUSIONS: Taken together, our results clearly demonstrate that treatment with Hypericum reduces the development of inflammation and tissue injury, events associated with periodontitis.